A Concurrent Entity Component System for Geographical Wildlife Epidemiological Modeling. Issue 4 (19th September 2020) - Davis, Austin V.; Wang, Shaowen
Abstract : North American bat species have been undergoing extreme population declines due to the White‐Nose Syndrome (WNS) epidemic caused by the spread of its pathogen, Pseudogymnoascus destructans . Existing models that represent the spread of the disease are limited in their scalability for use in management decisions or lacked the sophistication necessary to capture the complexity of WNS spread. Grounded in the theory of geoexpression, we exploit the latent structure of geographical process concurrency by implementing our modeling software using a concurrent Entity Component System architecture. We demonstrate our model's computational tractability for millions of individual bats. This work is significant because it lays the foundation for the use of advanced cyberinfrastructure and cyberGIS to address challenges in geographical wildlife epidemiology that can be understood using dynamic geographical Individual‐Based Models.